A COMPARATIVE-TYPOLOGICAL ANALYSIS OF KINSHIP TERMS IN ENGLISH, RUSSIAN, AND UZBEK LANGUAGES (A CASE STUDY OF THE CONCEPTS "AMAKI" AND "TOG’A") (Multidisciplinary Journal of Science and Technology, 2026)
In this article, the system of kinship terms in English, Russian and Uzbek languages is studied from a comparative-typological point of view. The main goal of the research is to determine the lexical-semantic features of kinship relations in different languages and to reveal their connection with cultural codes. In the work, the issues of inter-linguistic lacunae and semantic differentiation are highlighted through a comparative analysis of the terms "amaki" and "tog’a" with the English "uncle" and the Russian "дядя". As a result, the fact that the kinship system in the Uzbek language has a hierarchical and paternalistic character, and the dominance of linear and functional models in the English and Russian languages has been scientifically substantiated.